An Experimental Approach to Gastrojejunostomy on Rats for Better Gastric Emptying - Karataş, Cihan; Alim, Altan; Akıncı, Hakan; İlgün, Serkan (Cerrahpaşa Medical Journal, 2021)
Objective: Postsurgical gastroparesis is common morbidity following antecolic gastrojejunostomy. We aimed to find a solution for postsurgical gastroparesis with a modification of the operative technique using cross antecolic gastrojejunostomy. Methods: Twenty adult male rats were separated into 2 groups of 10 animals (classic antecolic gastrojejunostomy—group A and cross antecolic gastrojejunostomy—group B). By using a scintigraphic method on the second postoperative day, these 2 groups were compared for their gastric emptying rates. A 5 mCi Tc-99m pertechnetate scintigraphy scan was used for measuring the gastric emptying rate with a 6 F feeding tube at the 1st, 20th, and 45th minute and compared within areas of the anastomosis, cardia, body, and pylorus. The Mann– Whitney U-test was used for the statistical analysis. Results: When compared with group B at the 1st, 20th, and 45th minute, the radioactivity of Tc99m pertechnetate in the pylorus was significantly higher in group A. This likely suggests that gastric emptying rate was slower in group A than in group B. However, the gastric emptying rate of group B gradually decreased and was found to be more effective. Conclusion: Cross antecolic gastrojejunostomy may be a solution to improve gastric emptying in patients with postsurgical gastroparesis. Cite this article as: Karatas C, Alim A, Akıncı H, İlgün S. An experimental approach to gastrojejunostomy on rats for better gastric emptying. Cerrahpaşa Med J. 2021;45(3):147-151.